Studi Kinerja Pelat dan Balok Beton Bertulang di Gedung E Fakultas Teknik Universitas Lampung Akibat Getaran - Resmonida, Dhea Yulia; Helmi, Masdar; Alami, Fikri (Universitas Lampung, 2020)
In General, the plate of building will restrain the live load from various activities on it. Furthermore, this live load may produce structural vibrations which cause the inconvenient condition for the users. The study aims to evaluate the vibrations of the plate based on testing on fieldand numerical analysis using SAP2000 Software. The analysis calcutionsaccording to ISO 2631-2 : 2003 and steel design guide 11th series floor vibrations due to human activity The measurement on field shows that the compression strength of reinforced concrete for the plate and beams are between K-350 and K-400 which means both of them are medium quality concrete in addition. Thefrequencies of plate are between 12,94 - 23,29 Hz with the acceleration rates of 0,235 - 1,13 m/s². The numerical analysis results that the frequences of plate in 8,05 Hz and 8,13 Hz frequences due to walking load with the accelerations under 0,5% g. Based on both of analysis is concluded that the plate E building is a rigid structure. Keywords: Beam, Plate, Vibrations and Acceleration .